Development of a Novel Wasp-Inspired Friction-Based Tissue Transportation Device - Sakes, Aimée; van de Steeg, Ivo A.; de Kater, Esther P.; Posthoorn, Perry; Scali, Marta; Breedveld, Paul (Frontiers in Bioengineering and Biotechnology, 2020)
Currently existing tubular transportation systems for the extraction of large tissue masses during Minimal Invasive Surgery (MIS) are subjected to a large amount of operating limitations. In this study, a novel transportation mechanism (patented) was developed inspired by the egg-laying structure of wasps. The developed mechanism consists of an outer tube within which six reciprocating semi-cylindrical blades are present and tissue is transported using a friction differential between the blades. Two motion sequences were developed: (1) 1-5 motion sequence, in which one blade moves forward, while the remaining five blades move backwards and (2) 2-4 motion sequence, in which four blades move backward while two blades move forward. A proof-of-principle experiment was performed to investigate the effects of tissue elasticity, tissue heterogeneity, and the motion sequence on the transportation rate [mg/s], transportation efficiency [%], and transportation reliability [%]. The mean transportation rate and reliability was highest for the 9 wt% gelatine phantoms at 4.21 ± 0.74 mg/s and the 1-5 sequence at 100%, respectively. The prototype has shown that the friction-based transportation principle has the potential of becoming a viable and reliable alternative to aspiration as a transportation method within MIS.